Problems of Social Protection of The Population - Odiljon Shodiyev (European Science Publishing, 2023)
The article examines the current state of social protection systems and identifies the main problems and challenges faced in ensuring the well-being of the population. The authors argue that social protection policies have not been able to keep pace with the changing social and economic conditions, resulting in inadequate coverage, insufficient funding, and weak institutional capacity. Provides a comprehensive overview of the social protection system, including its legal framework, institutional structure, and key social programs. The authors also discuss the main challenges facing the system, such as the high level of informality in the labor market, inadequate funding, and weak coordination among government agencies. The article suggests several measures that could help address these challenges, including the expansion of social insurance programs, the strengthening of institutional capacity, and the development of a comprehensive social protection strategy. The authors argue that these measures would help improve the effectiveness and efficiency of the social protection system, and ensure that it is better equipped to respond to the needs of the population.
Keywords: social protection, population, challenges, institutions, funding, policies, labor market, strategy, well-being, effectiveness, efficiency.